A thermodynamic model for molten salt-water solutions – Application to a thermodynamic optimization of the Ca(NO3)2-KNO3-H2O system. (January 2019) - Chartrand, Patrice; Pelton, Arthur D.
Highlights: Thermodynamic model valid over entire composition range from H2 O to anhydrous salts. Hydrated cations and short-range-ordering taken into account. Complete review of all thermodynamic and phase diagrams data for Ca(NO3 )2 -KNO3 -H2 O system. Model parameters included in database to calculate phase equilibria in multicomponent salt-water systems. Abstract: A new thermodynamic model has been developed for molten salt-water solutions. The model applies particularly to salt-rich solutions but may be applied over the entire composition range from anhydrous salts to pure H2 O. The model is an extension of the two-sublattice Modified Quasichemical Model for molten anhydrous salt solutions with first-nearest-neighbour short-range ordering. The model assumes the existence of hydrated cations such as K(H2 O)j + and Ca(NO3 )k 2+ as well as "free" neutral H2 O molecules. The model has been used in a complete critical evaluation and thermodynamic optimization of the three binary systems KNO3 -Ca(NO3 )2, KNO3 -H2 O and Ca(NO3 )2 -H2 O and of the ternary system Ca(NO3 )2 -KNO3 -H2 O.